Pengaruh Kemandirian Belajar Terhadap Kreativitas Belajar Dalam Kaitannya Dengan Prestasi Belajar - Kesuma Wardani; Darsono Darsono; Pujiati Pujiati (Faculty of Teacher Training and Education, University of Lampung, 2017)
This study aims to determine whether there an influence of learning independence on learning creativity in relation to student achievement at class VII SMP Muhammadiyah 1 Metro. The research method used is descriptive verification with ex post facto approach. The population study is all students of grade VII at SMP Muhammadiyah 1 Metro, which amounted to 140 students, and the sample this study is 104 students. Hypothesis using linear regression test with path analysis. Based on data analysis, the following results are obtained. (1) There is an influence of class VII learning independence on the learning creativity of students. (2) There is an influence of learning creativity to learning achievement of IPS student of class VII. (3) There is influence of learning independence to learning achievement of IPS student of class VII. (4) There is am influence of learning independence to learning creativity of student learning class VIIstudent. (5) There is an influence of learning independence on IPS learning achievement through the creativity of students learning class VII.Penelitian ini bertujuan mengetahui ada tidaknya pengaruh kemandirian belajar terhadap kreativitas belajar dalam kaitannya dengan prestasi belajar siswa kelas VII SMP Muhammadiyah 1 Metro. Metode penelitian yang digunakan adalah deskriptif verifikatif dengan pendekatan ex post facto. Populasi penelitian adalah seluruh siswa-siswi kelas VII SMP Muhammadiyah 1 Metro yang berjumlah 140 siswa, dan sampel penelitian ini 104 siswa. Hipotesis menggunakan uji regresi linier dengan analisis jalur. Berdasarkan analisis data diperoleh Hasil sebagai berikut. (1) Ada pengaruh kemandirian belajar terhadap kreativitas belajar siswa kelas VII. (2) Ada pengaruh kreativitas belajar terhadap prestasi belajar IPS siswa kelas VII.(3) Ada pengaruh kemandirian belajar terhadap prestasi belajar IPS siswa kelas VII.(4) Ada pengaruh kemandirian belajar terhadap kreativitas belajar siswa kelas VII.(5) Ada pengaruh kemandirian belajar terhadap prestasi belajar IPS melalui kreativitas belajar siswa kelas VII.Kata kunci: kemandirian, kreativitas,prestasi belajar IPS